Acute Kidney Injury in Critically Ill Vascular Surgery Patients is Common and Associated with Increased Mortality - Harris, Donald G.; Koo, Grace; McCrone, Michelle P.; Weltz, Adam S.; Chiu, William C.; Sarkar, Rajabrata; Scalea, Thomas M.; Diaz, Jose J.; Lissauer, Matthew E.; Crawford, Robert S. (Frontiers in Surgery, 2015)
Introduction. Vascular surgery patients have multiple risk factors for renal dysfunction, but acute kidney injury (AKI) is poorly studied in this group. The purpose of this study was to define the incidence, risk factors and outcomes of AKI in high risk vascular patients. Methods. Critically ill vascular surgery patients admitted during January – December 2012 were retrospectively analyzed with 1-year follow-up. The endpoint was AKI by established RIFLE creatinine criteria. The primary analysis was between patients with or without AKI, with secondary analysis of postoperative AKI. Outcomes were inpatient and 1-year mortality, inpatient lengths of stay, and discharge renal function. Results. 136 vascular surgery patients were included, representing 27% of all vascular surgery admissions during the study period. 65 (48%) developed AKI. Independent global risk factors for AKI were diabetes, increasing critical illness severity, and sepsis. While intraoperative blood loss and hypotension were associated with subsequent renal dysfunction, postoperative AKI rates were similar for patients undergoing aortic, carotid, endovascular, or peripheral vascular procedures, All RIFLE grades of AKI were associated with worse outcomes. Overall, patients with AKI had significantly increased short and long-term mortality, longer inpatient lengths of stay, and worse discharge renal function. Conclusions. AKI is common among critically ill vascular surgery patients. Importantly, the type of surgical procedure appears to be less important than intra- and perioperative management in determining renal dysfunction. Regardless of its severity, AKI is a clinically significant complication that is associated with substantially worse patient outcomes.